2019
DOI: 10.1111/hiv.12823
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 genotype is independently associated with immunodeficiency progression among Chinese men who have sex with men: an observational cohort study

Abstract: ObjectivesHIV-1 genetic diversity is increasing among men who have sex with men (MSM) in China, but the association of HIV-1 genotype with disease progression remains to be elucidated. MethodsWe collected data in an observational longitudinal cohort study of 860 HIV-1-infected MSM in Guangzhou, China between January 2008 and March 2017. Kaplan-Meier analysis and Cox proportional hazard model were used to predict the time from HIV-1 diagnosis to immunodeficiency progression (CD4 cell count < 200 cells/ll) as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…More importantly, the risk group and age compositions of 07&08&C and CRF01_AE infected cases were quite similar (data not shown), suggesting the co-circulation of CRF01_AE and 07&08&C strains in similar population in Harbin. Extensive studies have demonstrated CRF07_BC infection exhibits a slow disease progression [34]. Consistent with this, our data indicated both median CD4 count and the proportion of CD4hi cases in 07&08&C cases were much higher than those in CRF01_AE cases.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…More importantly, the risk group and age compositions of 07&08&C and CRF01_AE infected cases were quite similar (data not shown), suggesting the co-circulation of CRF01_AE and 07&08&C strains in similar population in Harbin. Extensive studies have demonstrated CRF07_BC infection exhibits a slow disease progression [34]. Consistent with this, our data indicated both median CD4 count and the proportion of CD4hi cases in 07&08&C cases were much higher than those in CRF01_AE cases.…”
Section: Discussionsupporting
confidence: 90%
“…Several cohort studies in China have demonstrated that HIV-1 genotype was the independent variable associated with disease progression. CRF01_AE infection is commonly associated to lower baseline CD4 count, more rapid CD4 count decline and faster progression to immunode ciency than non-CRF01_AE infection in China [34][35][36]. Consistent with the above ndings, in this study, relative to non-CRF01_AE infection, CRF01_AE infection in Harbin had signi cantly lower odds of being CD4hi case.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies showed slower disease progression in subjects infected with CRF07_BC than subtype B or CRF01_AE [6,8,10,40]. Further investigation indicated that the above clinical findings may be associated with the deletion of 7-aa ( 30 PIDKELY 36 ) in p6 Gag [6,8].…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies indicated that patients infected with the CRF07_BC Δ7 variant exhibited lower viral loads and slower disease progression compared with individuals infected with HIV-1 subtype B or CRF01_AE [6][7][8][9][10]. Previous in vitro studies showed that HIV-1 isolates and the infectious clone of CRF07_BC with the Δ7 mutation displayed relatively lower replication capacity and slower replication kinetics than HIV-1 subtype B or Thai B' [7,8].…”
mentioning
confidence: 99%
“…This part of the population has the ability to cause widespread transmission of CRF08_BC. Just like since CRF07_BC was first discovered, it has spread rapidly among China provinces through the MSM population [44]. Taken together, these results indicated that prioritizing IDUs, MSM groups, lower education and young person's intervention was likely to be significantly effective in preventing spread of CRF08_BC [5,6,45].…”
Section: Factors Correlated With Clusteringmentioning
confidence: 99%